Ion and aerosol precursor densities in Titan's ionosphere: A multi‐instrument case study. Issue 10 (8th October 2016) - Shebanits, O.; Wahlund, J.‐E.; Edberg, N. J. T.; Crary, F. J.; Wellbrock, A.; Andrews, D. J.; Vigren, E.; Desai, R. T.; Coates, A. J.; Mandt, K. E.; Waite, J. H.
Abstract: The importance of the heavy ions and dust grains for the chemistry and aerosol formation in Titan's ionosphere has been well established in the recent years of the Cassini mission. In this study we combine independent in situ plasma (Radio Plasma and Wave Science Langmuir Probe (RPWS/LP)) and particle (Cassini Plasma Science Electron Spectrometer, Cassini Plasma Science Ion Beam Spectrometer, and Ion and Neutral Mass Spectrometer) measurements of Titan's ionosphere for selected flybys (T16, T29, T40, and T56) to produce altitude profiles of mean ion masses including heavy ions and develop a Titan‐specific method for detailed analysis of the RPWS/LP measurements (applicable to all flybys) to further constrain ion charge densities and produce the first empirical estimate of the average charge of negative ions and/or dust grains. Our results reveal the presence of an ion‐ion (dusty) plasma below 1100 km altitude, with charge densities exceeding the primary ionization peak densities by a factor ≥2 in the terminator and nightside ionosphere ( n e / n i ≤ 0.1). We suggest that ion‐ion (dusty) plasma may also be present in the dayside ionosphere below 900 km ( n e / n i < 0.5 at 1000 km altitude). The average charge of the dust grains (≥1000 amu) is estimated to be between −2.5 and −1.5 elementary charges, increasing toward lower altitudes. Key Points: Detection of electron‐depleted dusty ion‐ion plasma in lower ionosphere with enhanced densities First empirical estimate of the negative ion and dust grain charge